ROLE OF PANCHAKARMA IN MYASTHENIA GRAVIS - A CASE STUDY - H A, Ashwini; Goud, Kiran. M.; S J, Lolashri (International Journal of Ayurveda and Pharma Research, 2018)
Myasthenia Gravis (MG) is a long-term neuromuscular disease that leads to varying degrees of skeletal muscle weakness. The underlying defect is a decrease in the number of available acetylcholine receptors (AChRs) at neuromuscular junctions due to an antibody mediated autoimmune attack. The most commonly affected muscles are those of the eyes, face and swallowing. The cause of this disease can be understood in view of Upahata Dhatu Ushma, Srotas and Marutha respectively. The present observation was conducted with an objective to find out the efficacy of Ayurvedic management in Myasthenia gravis. Here is a case of 50years old Hindu female who was diagnosed as myasthenia gravis (MG) reported with complaining of slurred speech, low pitch of voice, difficulty to open the mouth and to swallow food and weakness in the both upper limbs since 4months was registered in OPD of SKAMCH&RC, Bengaluru. Considering the signs and symptoms patient was treated on the line of Ardita Vata chikitsa, Sarvanga Abhyanga with Moorchita tila taila, Nasya with Yashtimadhu taila, Gandusha with Erimedadi taila, Jihwa nirlekhana with Vacha churna were done. Treatment shows significant improvement in the symptoms without any side effects.